Genetic Analyses of the Arabidopsis ATG1 Kinase Complex Reveal Both Kinase-Dependent and Independent Autophagic Routes during Fixed-Carbon Starvation. Issue 12 (15th October 2019) - Huang, Xiao; Zheng, Chunyan; Liu, Fen; Yang, Chao; Zheng, Ping; Lu, Xing; Tian, Jiang; Chung, Taijoon; Otegui, Marisa S.; Xiao, Shi; Gao, Caiji; Vierstra, Richard D.; et al.
Abstract : Characterization of quadruple mutants eliminating ATG1 reveals that prolonged fixed-carbon starvation induces an ATG1 kinase-independent autophagic route in Arabidopsis. Abstract: Under nutrient and energy-limiting conditions, plants up-regulate sophisticated catabolic pathways such as autophagy to remobilize nutrients and restore energy homeostasis. Autophagic flux is tightly regulated under these circumstances through the AuTophaGy-related1 (ATG1) kinase complex, which relays upstream nutrient and energy signals to the downstream components that drive autophagy. Here, we investigated the role(s) of the Arabidopsis ( Arabidopsis thaliana ) ATG1 kinase during autophagy through an analysis of a quadruple mutant deficient in all four ATG1 isoforms. These isoforms appear to act redundantly, including the plant-specific, truncated ATG1t variant, and like other well-characterized atg mutants, homozygous atg1abct quadruple mutants display early leaf senescence and hypersensitivity to nitrogen and fixed-carbon starvations. Although ATG1 kinase is essential for up-regulating autophagy under nitrogen deprivation and short-term carbon starvation, it did not stimulate autophagy under prolonged carbon starvation. Instead, an ATG1-independent response arose requiring phosphatidylinositol-3-phosphate kinase (PI3K) and SUCROSE NONFERMENTING1-RELATED PROTEIN KINASE1 (SnRK1), possibly through phosphorylation of the ATG6 subunit within the PI3K complex by the catalytic KIN10 subunit of SnRK1. Together, our data connect ATG1 kinase to autophagy and reveal that plants engage multiple pathways to activate autophagy during nutrient stress, which include the ATG1 route as well as an alternative route requiring SnRK1 and ATG6 signaling.